Empirical Validation of a Hypothesis of the Hormetic Selective Forces Driving the Evolution of Longevity Regulation Mechanisms - Gomez-Perez, Alejandra; Kyryakov, Pavlo; Burstein, Michelle T.; Asbah, Nimara; Noohi, Forough; Iouk, Tania; Titorenko, Vladimir I. (Frontiers in Genetics, 2016)
Exogenously added lithocholic bile acid and some other bile acids slow down yeast chronological aging by eliciting a hormetic stress response and altering mitochondrial functionality. Unlike animals, yeast cells do not synthesize bile acids. We therefore hypothesized that bile acids released into an ecosystem by animals may act as interspecies chemical signals that generate selective pressure for the evolution of longevity regulation mechanisms in yeast within this ecosystem. To empirically verify our hypothesis, in this study we carried out a three-step process for the selection of long-lived yeast species by a long-term exposure to exogenous lithocholic bile acid. Such experimental evolution yielded 20 long-lived mutants, three of which were capable of sustaining their considerably prolonged chronological lifespans after numerous passages in medium without lithocholic acid. The extended longevity of each of the three long-lived yeast species was a dominant polygenic trait caused by mutations in more than two nuclear genes. Each of the three mutants displayed considerable alterations to the age-related chronology of mitochondrial respiration and showed enhanced resistance to chronic oxidative, thermal, and osmotic stresses. Our findings empirically validate the hypothesis suggesting that hormetic selective forces can drive the evolution of longevity regulation mechanisms within an ecosystem.